Investigating Critical Success Factors of Brand Loyalty: A Meta-Data Analysis Approach - Abd Aziz, Syahida; Jusoh, Muhammad Shahar; Amlus, Mohammad Harith (International Review of Management and Marketing, 2017)
Brand loyalty is a critical issue faced by organisations. It increases an organisation's profits and market share. Overlooking brand loyalty among customers raises problems in retaining customers. Besides, retaining the existing customers is more cost efficient rather than gaining and attracting new customers. Thus, this paper explores the elements of brand management that influence customer brand loyalty. This paper conducts a meta-data analysis addressing this lacuna in the literature and helps researchers to understand the concepts and elements used to measure customer brand loyalty. The study found that product quality, brand service quality, brand value and brand image, among others are factors influencing brand loyalty. Brand loyalty can be conceptualized with measurable brand dimensions and tested in future empirical studies for model fitness. Keywords: Brand Management, Brand Loyalty, Meta-Data analysis JEL Classifications: M1, M3